NGHIÊN CỨU SỰ TẠO THÀNH PHỨC CHẤT XÚC TÁC CỦA Co(II) VỚI AXETYLAXETON (Acac) TRONG HỆ: H2O – Co2+– Acac (1) - Huỳnh, Lê Văn; Khôi, Nguyễn Hữu; Xuyến, Nguyễn Văn; Tuyển, Nguyễn Minh (Vietnam Journal of Chemistry, 2012)
This paper presents our studied results on formating Co2+–Axetylaxetone (Acac) complex playing the role catalyst for catalaza reaction in the system: H2O–Co2 +–Acac. The formed complex has following characters: highly catalytic activity, electron absorption spectrum, composition and stability constant determined by some of physico-chemical methods.